Global shocks and risk to financial stability in Asia - Hans Genberg (Asian Development Bank Institute (ADBI), 2017)
Asian emerging market economies have recovered relatively well from the Great Recession of 2008-2009. Emerging Asia has been quite successful in maintaining both macroeconomic and financial stability in a turbulent global environment. Policy frameworks and governance structures have been adapted based on lessons learned from the Asian Financial Crisis. In general, policy makers have not been shy to adopt an eclectic approach to achieving monetary and financial stability using more than a single policy instruments to reach their objectives. Interventions in the foreign exchange markets are used in many jurisdictions to limit currency volatility, short-term interest rates are aimed at attaining macroeconomic stability interpreted mainly, but not exclusively, as price stability, and macroprudential policies have been employed in attempts to reduce the risk of financial stability. The use of multiple instruments to reach multiple goals is not without risk, however. At a minimum it requires coordination among the entities that are responsible for each instrument, which in turn necessitates proper governance both within the central bank and between the central bank and other agencies that may be involved. Including a wider set of objectives than price stability in the tasks assigned to central banks also raises questions about the ability of the central bank to reach these objectives while avoiding the pitfalls associated with trying to do so.
Keywords: E44; E61; F38; 330; Global shocks; emerging market economies; central bank policy strategies; external borrowing; capital flow measures; macroprudential policies